HISTORICAL OVERVIEW ON FLT METHODOLOGY - Poghosyan, Ofelya; Ghumashyan, Varduhi (Armenian Folia Anglistika, 2024)
Rapid changes in various spheres of the world and in the field of education in particular make the role of foreign language teaching and learning of paramount significance. In this regard, the study of the recent developments in the methods of foreign language teaching is not only crucial but also necessary, as sharing information is commonly implemented through language. The present research is meant to provide a comprehensive overview of the historical developments and an in-depth view of the latest advancements in foreign language teaching from both theoretical and practical perspectives with a focus on the use of innovative teaching strategies, approaches, styles and technology integration to enhance foreign language learning and teaching. This article is also aimed at shedding light on the importance of considering the requirements and needs of today’s learners when choosing the appropriate methods of teaching by teachers. Herein it is of primary concern to take into account the fact that due to manifold developments in different fields of human activity, language teaching undergoes different changes and requires new methods and approaches. In addition to all these factors, FL teaching and learning should be directed to the enhancement of intercultural competence, as it can help learners develop a more open-minded attitude towards different cultures. This work particularly highlights the necessity of changing the roles of FL teachers that reflect a shift towards a more learner-centered and technology-enhanced approach to language teaching and learning. These new roles are aimed to foster learner autonomy and critical thinking skills, to engage learners in active learning, and to create a positive learning environment. They also promote collaborative interactions among learners, recognizing and addressing their needs by providing learners with constructive feedback, authentic and varied language input.
Keywords: traditional method; teacher-centered; learner-centered; background knowledge; schemata; graphic organizer